Essays on Health and Retirement in Canada - Goshev, Simo (My University, 2008)
My dissertation is composed of an introductory chapter followed by three independent chapters focusing on two themes: health and retirement. The last chapter concludes. After the introductory chapter, the second chapter investigates whether self reported general stress is a mediator in the relationship between socio-economic status (SES) and health. I use a six-year long panel of the Canadian Survey of Labour and Income Dynamics and employ dynamic econometric modelling techniques to study men and women who are major income earners in their families. I find little evidence that general stress is a pathway from SES to health. While the results suggest a strong negative association between stress and health for both men and women, they provide little support to the hypothesis of a significant effect of income on stress, consistent with the direction of the SES-health gradient. The third chapter studies whether self-assessed health status (SAH) contains information about future mortality and morbidity, beyond the information that is contained in standard "observable" characteristics of individuals (including pre-existing diagnosed medical conditions). Using a ten-year span of the Canadian National Population Health Survey, we find evidence that SAH does contain private information for future mortality and morbidity. Moreover, the extra information in SAH is greater at older ages. Our results suggest that a shift from defined benefit to defined contribution pension arrangements may carry with it the cost of exacerbated adverse selection in the market for annuities, especially at older ages. That would make it more difficult for older individuals to insure longevity risk. The fourth chapter looks at whether differences in early retirement pathways are associated with differences in post-retirement outcomes of health, stress and dwelling tenure. I use a 5 ample of men from the Canadian Survey of Labour and Income Dynamics, years 1996 to 2004. I find that differences in pre-retirement health indicators (such as self-assessed health and disability), as pathways to early retirement, are likely to be associated with differences in post-retirement health and stress. In addition, the results suggest that "involuntary" retirees (men who may have retired because of health and/or health related coniitions) are more likely to experience worse post-retirement outcomes (in terms of health and stress) than men who retire "voluntarily". Retirement circumstances are found to have no statistically significant effect on dwelling tenure.
Keywords: health and retirement; socio-economic status; stress; self-assessed health status; true morbidity and mortality; Canadian National Population Health Survey; post-retirement health